Intestinal ischemia due to methamphetamine use: A case report. (2019) - Choi, Kihoon; Imrie, Andrew; Lourie, Rohan; Cross, Trent
Highlights: Methamphetamine is associated with non-occlusive intestinal ischemia. Splanchnic vasocontriction of mesenteric and colonic vessels is the most likely cause of methamphetamine-induced intestinal ischemia. Surgeons should have a high index of suspicion for intestinal ischemia in methamphetamine users who present with acute abdominal pain. Abstract: Introduction: Methamphetamine use is a rare cause of intestinal ischemia but is of clinical significance due to its high morbidity and mortality. Knowledge of methamphetamine-induced intestinal ischemia has been limited to few case reports. Case presentation: We describe the case of a 48-year-old man who presented with ischemic bowel related to methamphetamine use. With concern for intestinal infarction the patient was taken to the operating room for emergency laparotomy, which found a segmental gangrene of small bowel and colon. The patient subsequently underwent right hemicolectomy and small bowel resection for damage control, followed by second-look laparotomy and anastomosis. The patient recovered well from the surgery and was discharged without complications. Conclusion: This case report alerts surgeons to have a high index of suspicion for intestinal ischemia in methamphetamine users who present with acute abdominal pain.